A Review on Internet of Things Solutions for Intelligent Energy Control in Buildings for Smart City Applications. (March 2017) - Khajenasiri, Iman; Estebsari, Abouzar; Verhelst, Marian; Gielen, Georges
Abstract: A smart city exploits sustainable information and communication technologies to improve the quality and the performance of urban services for citizens and government, while reducing resources consumption. Intelligent energy control in buildings is an important aspect in this. The Internet of Things can provide a solution. It aims to connect numerous heterogeneous devices through the internet, for which it needs a flexible layered architecture where the things, the people and the cloud services are combined to facilitate an application task. Such flexible IoT hierarchical architecture model will be introduced in this paper with an overview of each key component for intelligent energy control in buildings for smart cities.